The application example of the sensitivity analysis of the solution to coefficients of the k-ε model - Błazik-Borowa, Ewa (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The paper presents the dependence between the degree of approximation of flow property functions and the sensitivity coefficients which are results of sensitivity analysis of solution to the coefficients of the k-ε turbulence model. It is shown that the model coefficients are factors of derivatives in the set of equations which describes the k-ε turbulence model. Because of this fact, when the term with the given parameter is large enough then the value of this parameter, being only the factor, has also larger influence on the solution. The numerical research is preceded by the description of calculation of sensitivity coefficients and their physical sense. The problem is presented for three tasks of incompressible steady flow around square and rectangular models with use of the standard and RNG versions of the k-ε turbulence model.